2022
DOI: 10.53894/ijirss.v5i4.743
|View full text |Cite
|
Sign up to set email alerts
|

Banking Risk in Selected MENA Countries

Abstract: This study examines the influence of bank-specific variables on the individual risk of 58 banks in ten MENA countries over the period 2011-2019. Firstly, investigating the correlations among the banks’ stock returns depicts that the banks with the highest correlations are in Saudi Arabia, the United Arab Emirates, and Qatar, either domestically or across countries. Then, the individual bank risk ranking for the entire sample based on estimated historical Value-at-Risk (VaR) and Estimated Shortfall (ES) shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The Basel Banking Supervision Committee was established under the aegis of the Bank for International Settlements (BIS) to guarantee central bank coordination and carry out a uniform strategy for banking regulations. Since its establishment, the committee has grown into a significant advisory and decision-making body for banking regulations that can be implemented globally (Gadou, 2022;Tiryaki & Yılmaz, 2012).…”
Section: Financial Regulation and Banking Regulationsmentioning
confidence: 99%
“…The Basel Banking Supervision Committee was established under the aegis of the Bank for International Settlements (BIS) to guarantee central bank coordination and carry out a uniform strategy for banking regulations. Since its establishment, the committee has grown into a significant advisory and decision-making body for banking regulations that can be implemented globally (Gadou, 2022;Tiryaki & Yılmaz, 2012).…”
Section: Financial Regulation and Banking Regulationsmentioning
confidence: 99%
“…Without considering macroeconomic factors as determinants of this risk, some other studies have focused more on bank characteristics to measure the impact of specific factors on liquidity risk. Abbas and Mourouj (2015); Ajibike and Aremu (2015); Alshatti (2015); Gadou (2022); Marozva (2015); Saleh and Abu Afifa (2020); Zaghdoudi and Hakimi (2017) have found that liquidity risk increases the financial performance of banks. Most studies focus on a single location and use return on assets, return on equity, return on capital employed and net interest margin as variables to represent bank financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A Central Bank Digital Currency involves two possible designs: (a) an account-based Central Bank Digital Currency and (b) a token-based (or value-based) Central Bank Digital Currency. These designs correspond to the two existing types of central bank money and their corresponding payment systems (Gadou, 2022;Kahn & Roberds, 2009) central bank reserves (in an account-based system) and banknotes (in a token-based system). A payment is made if a monetary asset is transferred from a payer to a payee.…”
Section: Benefits Of Implementing a Central Bank Digital Currency In ...mentioning
confidence: 99%